ANALYSIS OF COMPETENCE AND COMMUNICATION ON TEACHER PERFORMANCE WITH TRAINING AS AN INTERVENING VARIABLE AT SMP NEGERI 1 BUKIT BENER MERIAH REGENCY - Karmila; Mesra B; Kiki Farida Ferine (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of competence and communication on teacher performance with training as an intervening variable at SMP Negeri 1 Bukit, Bener Meriah Regency. The background of this study is based on the important role of teachers in improving the quality of education and the need for optimal teacher performance through increased competence, communication skills, and relevant training. This study used a quantitative approach with a population of 71 teachers, consisting of ASN and PPPK, which were designated as saturated samples. Data analysis was conducted using Partial Least Square (PLS) through SmartPLS. The results showed that competence had a positive and significant effect on teacher performance, while the influence of competence on training had a positive but insignificant effect. Communication skills had a significant effect on training, but a positive but insignificant effect on teacher performance directly. Training was proven to have a positive and significant effect on teacher performance. These findings indicate that increased training plays a mediator in strengthening the relationship between communication and teacher performance. This study recommends the need for a structured and sustainable training program to support the development of teacher competence and communication skills to optimally improve performance.